Design and synthesis of diazine-based panobinostat analogues for HDAC8 inhibition - Balasubramaniam, Sivaraman; Vijayan, Sajith; Goldman, Liam V.; May, Xavier A.; Dodson, Kyra; Adhikari, Sweta; Rivas, Fatima; Watkins, Davita L.; Stoddard, Shana V. (Beilstein Journal of Organic Chemistry, 2020)
Guided by computational analysis, herein we report the design, synthesis and evaluation of four novel diazine-based histone deacetylase inhibitors (HDACis). The targets of interest (TOI) are analogues of panobinostat, one of the most potent and versatile HDACi reported. By simply replacing the phenyl core of panobinostat with that of a diazine derivative, docking studies against HDAC2 and HDAC8 revealed that the four analogues exhibit inhibition activities comparable to that of panobinostat. Multistep syntheses afforded the visualized targets TOI1, TOI2, TOI3-rev and TOI4 whose biological evaluation confirmed the strength of HDAC8 inhibition with TOI4 displaying the greatest efficacy at varying concentrations. The results of this study lay the foundation for future design strategies toward more potent HDACis for HDAC8 isozymes and further therapeutic applications for neuroblastoma.
Keywords: diazine; histone deacetylase; inhibitors; isozymes; panobinostat

(untitled) - Strahl, B. D.; Allis, C. D. (Nature, 2000)

(untitled) - Barneda-Zahonero, B.; Parra, M. (Mol. Oncol., 2012)

(untitled) - Manal, M.; Chandrasekar, M. J. N.; Gomathi Priya, J.; Nanjan, M. J. (Bioorg. Chem., 2016)

(untitled) - Chakrabarti, A.; Oehme, I.; Witt, O.; Oliveira, G.; Sippl, W.; Romier, C.; Pierce, R. J.; Jung, M. (Trends Pharmacol. Sci., 2015)

(untitled) - Ingham, O. J.; Paranal, R. M.; Smith, W. B.; Escobar, R. A.; Yueh, H.; Snyder, T.; Porco, J. A., Jr; Bradner, J. E.; Beeler, A. B. (ACS Med. Chem. Lett., 2016)

(untitled) - West, A. C.; Johnstone, R. W. (J. Clin. Invest., 2014)

(untitled) - Ononye, S. N.; van Heyst, M.; Falcone, E. M.; Anderson, A. C.; Wright, D. L. (Pharm. Pat. Anal., 2012)

(untitled) - Glaser, K. B. (Biochem. Pharmacol., 2007)

(untitled) - Prince, H. M.; Bishton, M. J.; Johnstone, R. W. (Future Oncol., 2009)

(untitled) - Garnock-Jones, K. P. (Drugs, 2015)

(untitled) - Atadja, P. (Cancer Lett., 2009)

(untitled) - Stoddard, S. V.; May, X. A.; Rivas, F.; Dodson, K.; Vijayan, S.; Adhika, S.; Parker, K.; Watkins, D. L. (Mol. Inf., 2019)

(untitled) - Zhang, Y.; Feng, J.; Jia, Y.; Xu, Y.; Liu, C.; Fang, H.; Xu, W. (Eur. J. Med. Chem., 2011)

(untitled) - Lee, H.-Y.; Lee, J.-F.; Kumar, S.; Wu, Y.-W.; HuangFu, W.-C.; Lai, M.-J.; Li, Y.-H.; Huang, H.-L.; Kuo, F.-C.; Hsiao, C.-J.; Cheng, C.-C.; Yang, C.-R.; et al. (Eur. J. Med. Chem., 2017)

(untitled) - Chen, Y.; Wang, X.; Xiang, W.; He, L.; Tang, M.; Wang, F.; Wang, T.; Yang, Z.; Yi, Y.; Wang, H.; Niu, T.; Zheng, L.; et al. (J. Med. Chem., 2016)

(untitled) - Guo, Z. (Acta Pharm. Sin. B, 2017)

(untitled) - Flefel, E.; Tantawy, W.; El-Sofany, W.; El-Shahat, M.; El-Sayed, A.; Abd-Elshafy, D. (Molecules, 2017)

(untitled) - Martins, P.; Jesus, J.; Santos, S.; Raposo, L.; Roma-Rodrigues, C.; Baptista, P.; Fernandes, A. (Molecules, 2015)

(untitled) - Robarge, K. D.; Lee, W.; Eigenbrot, C.; Ultsch, M.; Wiesmann, C.; Heald, R.; Price, S.; Hewitt, J.; Jackson, P.; Savy, P.; Burton, B.; Choo, E. F.; et al. (Bioorg. Med. Chem. Lett., 2014)

(untitled) - Banerjee, S.; Adhikari, N.; Amin, S. A.; Jha, T. (Eur. J. Med. Chem., 2019)

(untitled) - Wolfson, N. A.; Pitcairn, C. A.; Fierke, C. A. (Biopolymers, 2013)

(untitled) - Rettig, I.; Koeneke, E.; Trippel, F.; Mueller, W. C.; Burhenne, J.; Kopp-Schneider, A.; Fabian, J.; Schober, A.; Fernekorn, U.; von Deimling, A.; Deubzer, H. E.; Milde, T.; et al. (Cell Death Dis., 2015)

(untitled) - Oehme, I.; Deubzer, H. E.; Wegener, D.; Pickert, D.; Linke, J.-P.; Hero, B.; Kopp-Schneider, A.; Westermann, F.; Ulrich, S. M.; von Deimling, A.; Fischer, M.; Witt, O. (Clin. Cancer Res., 2009)

(untitled) - Kushner, B. H. (J. Nucl. Med., 2004)

(untitled) - Brodeur, G. M. (Nat. Rev. Cancer, 2003)

(untitled) - Kolbinger, F. R.; Koeneke, E.; Ridinger, J.; Heimburg, T.; Müller, M.; Bayer, T.; Sippl, W.; Jung, M.; Gunkel, N.; Miller, A. K.; Westermann, F.; Witt, O.; et al. (Arch. Toxicol., 2018)

(untitled) - Banerjee, S.; Adhikari, N.; Amin, S. A.; Jha, T. (Eur. J. Med. Chem., 2019)

(untitled) - Di Micco, S.; Chini, M. G.; Terracciano, S.; Bruno, I.; Riccio, R.; Bifulco, G. (Bioorg. Med. Chem., 2013)

(untitled) - Leach, A. R.; Shoichet, B. K.; Peishoff, C. E. (J. Med. Chem., 2006)

(untitled) - Ewing, T. J. A.; Makino, S.; Skillman, A. G.; Kuntz, I. D. (J. Comput.-Aided Mol. Des., 2001)

(untitled) - Lauffer, B. E. L.; Mintzer, R.; Fong, R.; Mukund, S.; Tam, C.; Zilberleyb, I.; Flicke, B.; Ritscher, A.; Fedorowicz, G.; Vallero, R.; Ortwine, D. F.; Gunzner, J.; et al. (J. Biol. Chem., 2013)

(untitled) - Vannini, A.; Volpari, C.; Filocamo, G.; Casavola, E. C.; Brunetti, M.; Renzoni, D.; Chakravarty, P.; Paolini, C.; De Francesco, R.; Gallinari, P.; Steinkuhler, C.; Di Marco, S. (Proc. Natl. Acad. Sci. U. S. A., 2004)

(untitled) - Finnin, M. S.; Donigian, J. R.; Cohen, A.; Richon, V. M.; Rifkind, R. A.; Marks, P. A.; Breslow, R.; Pavletich, N. P. (Nature, 1999)

(untitled) - Rouanet-Mehouas, C.; Czarny, B.; Beau, F.; Cassar-Lajeunesse, E.; Stura, E. A.; Dive, V.; Devel, L. (J. Med. Chem., 2017)

(untitled) - Grandberg, I. I. (Chem. Heterocycl. Compd., 1974)

(untitled) - Wang, C.; Eessalu, T. E.; Barth, V. N.; Mitch, C. H.; Wagner, F. F.; Hong, Y.; Neelamegam, R.; Schroeder, F. A.; Holson, E. B.; Haggarty, S. J.; Hooker, J. M. (Am. J. Nucl. Med. Mol. Imaging, 2013)

(untitled) - Wang, H.; Yu, N.; Chen, D.; Lee, K. C. L.; Lye, P. L.; Chang, J. W. W.; Deng, W.; Ng, M. C. Y.; Lu, T.; Khoo, M. L.; Poulsen, A.; Sangthongpitag, K.; et al. (J. Med. Chem., 2011)

(untitled) - Gravel, M.; Touré, B. B.; Hall, D. G. (Org. Prep. Proced. Int., 2004)

(untitled) - Kawasaki, T.; Nakaoda, M.; Takahashi, Y.; Kanto, Y.; Kuruhara, N.; Hosoi, K.; Sato, I.; Matsumoto, A.; Soai, K. (Angew. Chem., Int. Ed., 2014)

(untitled) - Ha, S.-D.; Reid, C.; Meshkibaf, S.; Kim, S. O. (J. Biol. Chem., 2016)

(untitled) - Jain, A. N. (J. Comput.-Aided Mol. Des., 2007)

(untitled) - Jain, A. N. (J. Med. Chem., 2003)

(untitled) - Jain, A. N. (J. Comput.-Aided Mol. Des., 1996)

(untitled) - Pettersen, E. F.; Goddard, T. D.; Huang, C. C.; Couch, G. S.; Greenblatt, D. M.; Meng, E. C.; Ferrin, T. E. (J. Comput. Chem., 2004)

(untitled) - Warren, G. L.; Andrews, C. W.; Capelli, A.-M.; Clarke, B.; LaLonde, J.; Lambert, M. H.; Lindvall, M.; Nevins, N.; Semus, S. F.; Senger, S.; Tedesco, G.; Wall, I. D.; et al. (J. Med. Chem., 2006)